A FORMAÇÃO CONTINUADA DE PROFESSORES ALFABETIZADORES: do Pró-Letramento ao PNAIC - Salomão, Rommy (2014)
This research aims to study the educational policies focused to the continuing education of teachers in the early years of Elementary School. This research analyzes the process of establishing and implementing the actions developed by the Federal Government, in order to contribute to the overcoming of the difficulties of literacy teachers in the teaching and learning process. Considering the context in which the teachers are, in relation to the continuing education formation held by the Federal Government, the developing of this research has focused mainly on the analysis of the implementation of the National Pact for Literacy in the Correct Age, that began with the execution of the work of continuing education with the teachers of public schools in Ponta Grossa city – PR, this year (2013). Thus, this research has as North, the following problem: How did the process of implementation of National Pact for Literacy in the Correct Age, from the consolidation of Pro-Literacy Program happen? To answer the question raised, it was defined as specific objectives: contextualization of the establishment of the public educational policies to the continuing formation of teachers from the 1990s in Brazil; identification of the aspects of Pro-Literacy Program, that were determinants to the implementation of PNAIC; identification of the proposed implementation of the National Pact for Literacy in the Correct Age for the continuing education formation of literacy teachers. In order to understand the dimensions that underlie the continuing formation of teachers, it has started from the elaboration of a theoretical and methodological framework, which allows us to understand the historical context and its determinants. Thus, the theoretical and methodological axis is expressed by means of historical and dialectical materialism, which allows us to reveal the reality from the seizure of its contradictions in its totality. The methodological procedures adopted were based on theoretical bibliographic research of the main productions that deal with the studied subject. The bibliographic research was used as the theoretical base to ground the study of the subject ad it was based on authors that discuss about the State reform and about the educational policies. The documental research used primary sources (legislation), which will allow the understanding of the consolidation process of the Pro-Literacy Program in the context of the educational policies for the continuing education formation of the early years, as well as the process of implementation of the National Pact for Literacy in the Correct Age. It was concluded that the continuing education of teachers provides opportunities for actors training and updating of knowledge that are constantly changing in society, making the educational activity promotes human emancipation, helping the individual to have effective participation in society while transforming their reality.